1990
DOI: 10.1063/1.104276
|View full text |Cite
|
Sign up to set email alerts
|

Hertzian stress contribution to low friction behavior of thin MoS2 coatings

Abstract: Friction coefficients were measured for bearing materials slid in dry air against sputter-deposited MoS2-coated substrates. Ball versus flat tests were performed over a wide range of initial Hertzian pressures (200–1500 MPa) by varying loads (1–50 N), elastic moduli (70–615 GPa), and ball diameters (1.6–12.7 mm). The friction coefficient μ decreased as load L increased according to μ∝ L(−0.32), in agreement with the Hertzian contact model. Regression analysis of over 600 data points for friction coefficient ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
117
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(140 citation statements)
references
References 18 publications
22
117
1
Order By: Relevance
“…The process was carried out for densities ranging from 2.7 to 3.4g/cm 3 , leading to different energies. We found that lower cooling rates decrease the energy of DLC structures, leading to stable DLC structures with densities of 3.0 to 3.3g/cm 3 . In this study, we discuss the 3.24 g/cc system (the experimental value).…”
Section: The Atomistic Structure Of Bulk Ta-c Dlcmentioning
confidence: 93%
See 4 more Smart Citations
“…The process was carried out for densities ranging from 2.7 to 3.4g/cm 3 , leading to different energies. We found that lower cooling rates decrease the energy of DLC structures, leading to stable DLC structures with densities of 3.0 to 3.3g/cm 3 . In this study, we discuss the 3.24 g/cc system (the experimental value).…”
Section: The Atomistic Structure Of Bulk Ta-c Dlcmentioning
confidence: 93%
“…This simplified model assumes that the real contact area corresponds to the Hertzian zone, as calculated in equation (3). This assumption has been verified for soft and very thin interface films that lead to good accommodation in the contact geometry.…”
Section: Survey On Extremely Low Friction Under Boundary Lubricationmentioning
confidence: 99%
See 3 more Smart Citations